(untitled) (Bangladesh Journal of Otorhinolaryngology, 2014)
Objectives: To determine the relationship between social factors and frequency of CSOM & its extracranial complications and their clinical presentation. Methods: This cross-sectional study was carried out in the Department of Otolaryngology Head and Neck Surgery, Sir Salimullah Medical College & Mitford Hospital and Dhaka Medical College Hospital from 1st July 2009 to 30th June 2010. Results: In this study male (59%), lower class people (57%), age 11-20 years, resident in rural area (66%) and less educated patients were more affected. Having bath in the pond and/or river suffers more. Clinical presentation of CSOM and complication were aural discharge (100%), hearing impairment (94%), post auricular swelling (45%), pain in the ear (21%), postauricular discharge (27%), tinnitus (11%), vertigo (9%), headache (07%) and mass in the EAC (12%). Here found aural discharge mostly malodorous and scanty, attic perforation and cholesteatoma. Post auricular abscess most common (47%) extracranial complication and labyrinthitis is the lowest (3%). Atticoantral variety was more common (89%). Conclusion: Lower class people of rulal area, children and less educated personals were affected more with CSOM and its extracranial complications. So proper awareness among all level of people including medical practitioners can enhance prompt diagnosis and treatment and reduce the complication. DOI: http://dx.doi.org/10.3329/bjo.v19i2.17633 Bangladesh J Otorhinolaryngol 2013; 19(2): 104-109